2017
DOI: 10.3389/fphys.2017.00583
|View full text |Cite
|
Sign up to set email alerts
|

Human Biomechanical and Cardiopulmonary Responses to Partial Gravity – A Systematic Review

Abstract: The European Space Agency has recently announced to progress from low Earth orbit missions on the International Space Station to other mission scenarios such as exploration of the Moon or Mars. Therefore, the Moon is considered to be the next likely target for European human space explorations. Compared to microgravity (μg), only very little is known about the physiological effects of exposure to partial gravity (μg < partial gravity <1 g). However, previous research studies and experiences made during the Apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 64 publications
1
54
0
1
Order By: Relevance
“…It can be considered as an ideal case of an unmodulated BWS [12]. Since the SW and SLIP models do not have distributed mass, the CF BWS strategy also emulates the effects of reduced gravity for these models [14]. However, this is not the case for the MR model [23] due to the presence of limb mass.…”
Section: Constant-force Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be considered as an ideal case of an unmodulated BWS [12]. Since the SW and SLIP models do not have distributed mass, the CF BWS strategy also emulates the effects of reduced gravity for these models [14]. However, this is not the case for the MR model [23] due to the presence of limb mass.…”
Section: Constant-force Systemmentioning
confidence: 99%
“…These devices use active control in order to render a constant force. Note that this is still different from actual simulated gravity because the load is applied only to the upper body (distributed via the harness), and not in a distributed way on each single body segment [14]. Accurate investigations for swing phase therefore generally require set-ups similar to a parabolic space flight [15,16], which are inconvenient to reproduce.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, after space mission, detrimental effects on the musculoskeletal system due to the loss of muscle mass and muscle strength may also affect mental health and recovery [123]. Partial/micro gravity exposure has immediate effects on gait characteristics that include reduction of GRFs, stance phase duration, stride frequency, stride length, and walkto-run transition speed [124]. After a long-term exploration in space, the astronauts who completed missions within two weeks still exhibited increased variability in ankle and knee joints [125].…”
Section: H) Mood Disorders In Extreme Environmentsmentioning
confidence: 99%
“…The project started a few systematic reviews 1‐3 around specific questions in aerospace medicine that highlighted some issues around systematic reviews and primary studies in aerospace medicine. The methods to synthesize evidence on a focused health research question are well documented in the literature 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The methods to synthesize evidence on a focused health research question are well documented in the literature 4,5 . However, there are specific challenges in reviews of aerospace medicine that we observed in previous reviews, 1,2 like databases and resources to search for studies (Table 1). The other issues are highlighted in Table 2.…”
Section: Introductionmentioning
confidence: 99%